Investigations in the molecular events of transitional cell carcinoma of the bladder - Kadhim, Haider Sabah; Abdulamir, Ahmed Sahib; Hafidh, Rand Riadh; Abu Bakar, Fatimah; Abbas, Kassim Ali (Science Publications, 2008)
Problem Statement: Transitional Cell Carcinoma (TCC) of the bladder is a significant health problem worldwide. The molecular mechanisms of tumor development and progression are complicated but likely involve the interaction of tumor suppressor genes, oncogenes, cell cycle regulatory proteins and other factors. Hence this study tries to explore the role of p53, bcl-2, c-myc and Ki-67 in TCC of the bladder in correlation with different clinicopathological criteria which are tumor grade, muscle invasion by the tumor and disease presentation, primary or recurrent tumor. Approach: Thirty patients with TCC of the bladder were involved in the period from March 2007 - May 2008. Tumors were diagnosed by histopathology and compared with 20 control subjects. The expressions of p53, bcl-2, c-myc and Ki-67 proteins were investigated by immunohistochemistry (IHC). Results: Increased expression of p53 and bcl-2 was associated with tumor grade and muscle invasion (p<0.05), but not with disease presentation (p>0.05). C-myc expression was only associated with muscle invasion (p<0.05). Ki-67 was associated with tumor grade, muscle invasion and tumor presentation (p<0.05). The correlation among these cell cycle proteins was generally significantly positive except for the correlation between bcl-2 and c-myc was poor. Conclusions: There was a significant oncogenic role of p53 and bcl-2 on TCC in terms of muscle invasion and tumor grade. C-myc was associated only with tumor invasiveness and Ki-67 proved to act as a reliable prognostic factor of TCC. This could highlight the hot targets of TCC anti-cancer therapy and the reliable targets for disease prognosis.